Hubungan Interaksi Sosial Dengan Tingkat Depresi Pada Lansia Di Panti Sosial Tresna Werdha Budi Sejahtera Provinsi Kalimantan Selatan - Theresia Jamini; Fandi Jumaedy; Dwi Martha Agustina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Health problems often occur in the elderly, which affect social interactions. This condition can be one of the triggers for depression in the elderly in the nursing home. The incidence of depression experienced by the elderly who live in the study location is 50-75% due to loneliness, hopelessness, loss of a spouse, and loss of social roles. This type of research is a quantitative non-experimental, correlational research design with a cross-sectional approach. A total of 75 respondents at the Panti Sosial Tresna Werdha Budi Sejahtera, Banjarbaru, South Kalimantan, were taken by purposive sampling technique, and in this study, a questionnaire was used as a research instrument. The statistical test used the Spearman Rank Correlation at a significant level of 0.05 and the results showed that 32 respondents had sufficient social interaction and 32 respondents had a moderate depression level. The results of statistical tests using the Spearman Rank correlation obtained the Correlation Coefficient value of 0.580 and a p-value of 0.000.